The Importance of Needs Assessment in Medical Studies at El Marj University: An Analysis of Students’ Perspectives on Their Needs for an Effective ESP Course - Rim Mohammed Lasheiky; Dalal Ali Mohammed (المجلة الأفروآسيوية للبحث العلمي, 2024)
Recent studies emphasize the importance of English for specific purposes (ESP) needs assessments in enhancing educational outcomes for medical students, as these assessments enable instructors to tailor language instruction to address specific healthcare needs. Effective ESP programs equip students with essential language skills for patient care and professional collaboration. This research employed a descriptive analysis through mixed-methods approach, utilizing questionnaires and interviews to gather data. The study involved 60 medical students, and quantitative and qualitative analyses were conducted. Research shows that medical students need an ESP program focused on improving vocabulary, reading skills, and speaking abilities through vocabulary practice, providing more chances for practical application, and dedicating enough instructional time These insights guide the development of more targeted and effective ESP curricula to meet the specific linguistic demands of medical education.